2019
DOI: 10.1016/j.eats.2019.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Closing Wedge Proximal Tibial Osteotomy for Slope Correction in Failed ACL Reconstructions

Abstract: Increased sagittal plane posterior tibial slope has been identified as a risk factor for primary anterior cruciate ligament reconstruction (ACLR) failure. Although ACLR failure is multifactorial, correction of sagittal plane posterior tibial slope should be evaluated in patients with an ACLR graft rupture. There are limited technical descriptions of proposed decreasing tibial slope osteotomy procedures; therefore, the purpose of this Technical Note is to describe the current senior author's technique of perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
69
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 15 publications
1
69
0
3
Order By: Relevance
“…Many studies have shown the association between steep posterior tibial plateau slope and risk of ACL graft failure. [5][6][7]10 The one-stage arthroscopic approach described here combines (1) ACL reconstruction or (2) reduction and fixation of tibial spine avulsion, with a concomitant arthroscopy-assisted reduction of a PLTP fracture that restores the anatomic slope of the tibial plateau. Performing this one-stage procedure may help avoid the need for a subsequent slope-correcting osteotomy, and can help reduce postoperative morbidity and the overall rehabilitation period.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Many studies have shown the association between steep posterior tibial plateau slope and risk of ACL graft failure. [5][6][7]10 The one-stage arthroscopic approach described here combines (1) ACL reconstruction or (2) reduction and fixation of tibial spine avulsion, with a concomitant arthroscopy-assisted reduction of a PLTP fracture that restores the anatomic slope of the tibial plateau. Performing this one-stage procedure may help avoid the need for a subsequent slope-correcting osteotomy, and can help reduce postoperative morbidity and the overall rehabilitation period.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has demonstrated the association between steep posterior tibial plateau slope with an increased risk of ACL rupture, [2][3][4] as well as a significantly increased risk of graft failure of the reconstructed ACL. [3][4][5] In fact, a recent study by Grassi et al 4 has shown that the most accurate predictor of ACL graft failure was a steep PLTP slope measuring greater than 7.4 . Therefore, in cases of PLTP fracture occurring in the context of a "high-energy ACL" injury, initial recognition and surgical restoration of the anatomic PLTP slope represents a crucial opportunity to prevent failure of the reconstructed ACL.…”
mentioning
confidence: 99%
See 3 more Smart Citations